Aspek Inkoatif dalam Novel Absolute Duo - Diyah Ratnasari, Anak Agung; Artana, I Nyoman; Budiana, I Made (Humanis; Vol 20 No 1 (2017), 2017)
The title of this research is “The Inchoative Aspect in Absolute Duo’s Novel By Hiragi Takumi”. This research aimed is to find out, the formation, the variety, and the meaning of inchoative aspect in Absolute Duo’s Novel by Hiragi Takumi. The theories that used to analyze this study are syntax by Chaer (2012) and semantics by Pateda (2001).The result of the research shows the combination of two verbs with the suffix {~hajimeru}, {~dasu}, {~kakeru} may form the inchoative aspect. There are three kinds of  inchoative  aspect found in this study such as unfinished inchoative aspect, finished  inchoative aspect, and inchoative aspect has started towards the end not the past. Furthermore, the three variations show the meaning of  inchoative aspect is different.